Effects of auriculotherapy on stress, anxiety and depression in adults and older adults: a systematic review - Corrêa, Hérica Pinheiro; Moura, Caroline de Castro; Azevedo, Cissa; Bernardes, Mariana Ferreira Vaz Gontijo; Mata, Luciana Regina Ferreira Pereira da; Chianca, Tânia Couto Machado (Revista da Escola de Enfermagem da USP, 2020)
Objective To identify evidence in scientific literature about the effects of auriculotherapy for treating stress, anxiety and depression in adults and older adults by analyzing the main protocols for applying the intervention. Method A systematic review was performed following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA). Detailed individual search strategies were applied in February 2019 in the BDENF, CINAHL, Cochrane, CUMED, Embase, LILACS, PEDro, PubMed, Scopus, Segunda Opinião Formativa (SOF) and Web of Science databases. The methodological quality of the studies was assessed using the Jadad Scale. Results A total of 24 from the 859 articles found comprised the study sample. Of these, 22 (92%) showed a positive effect of auriculotherapy for stress, anxiety or depression. Conclusion The available evidence on the effects of auriculotherapy on stress, anxiety and depression proves the effectiveness of the technique in adults and older adults. However, the studies showed methodological weaknesses. Although the identified protocols are different, there are frequent similar points including Shenmen, Kidney, Autonomic Nervous System, Heart, Brain Stem and Liver 1 and 2 which can be used in new studies.